The current state of wearable device use in Parkinson's disease: a survey of individuals with Parkinson's - Hirczy, Siegfried; Zabetian, Cyrus; Lin, Yi-Han (Frontiers in Digital Health, 2024)
BackgroundInterest in wearable device use in Parkinson's disease (PD) has grown rapidly with many compelling studies supporting diagnostic and therapeutic uses. Concurrently, consumer devices have proliferated and their role in health and wellness has expanded. However, incorporation of consumer and medical wearable devices into medical care has in our experience been limited.ObjectiveWe sought to assess the current state of consumer and medical wearable device use among those with PD and to understand the factors impacting their rate of use.MethodsAn anonymous online survey of individuals with PD in the US was conducted from July 9th, 2023, to Jan 8th, 2024, with 298 completed responses collected.ResultsGreater than 90% of respondents were interested in new technologies with 67% having had experiences with consumer wearable devices. Only 24% were using consumer devices for disease management and many functions were not fully utilized. Medical wearable device use was very limited with only 8% having used a device. Users of both consumer and medical wearables generally reported low barriers to use despite continued strong perceptions on the importance of cost, impact on care, comfort, and other factors.ConclusionThis study demonstrates that for the clinical management of PD there is limited use of wearable devices even among individuals who are motivated and experienced with consumer wearable device use. Additionally, it is suggested that substantial barriers to medical wearable use are likely originating from the provider and/or systemic level.